2013
DOI: 10.1262/jrd.2012-090
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Lymphatic Vessel Formation Factors in PGF<sub>2α</sub>-induced Luteolysis in the Cow

Abstract: Prostaglandin F2α (PGF2α) induces luteolysis in cows and causes infiltration of immune cells, which resembles inflammatory immune response. Since the general immune response is mediated by the lymphatic system, we hypothesized that luteolysis is associated with generation of an immune response that involves lymphatic vessels in the bovine corpus luteum (CL). The CL was obtained from Holstein cows at the mid-luteal phase (days 10–12, ovulation = day 0) by ovariectomy at various time points after PGF2α injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…There was no difference in the mRNA expression of TNFA between the LPS and the CON cycle. Following PGF 2α -induced luteolysis, TNFA increased significantly after 15 min but returned to initial values within 12 h (Nitta et al, 2013). It is possible that the reason we could not detect the increase in luteal TNFA was the variable time (relative to biopsy) of LPS-induced luteolysis.…”
Section: Discussionmentioning
confidence: 81%
“…There was no difference in the mRNA expression of TNFA between the LPS and the CON cycle. Following PGF 2α -induced luteolysis, TNFA increased significantly after 15 min but returned to initial values within 12 h (Nitta et al, 2013). It is possible that the reason we could not detect the increase in luteal TNFA was the variable time (relative to biopsy) of LPS-induced luteolysis.…”
Section: Discussionmentioning
confidence: 81%
“…Elevated expression of PTGFR mRNA and protein has been observed in CLs on day 12 of pregnancy compared to day 12 of the estrous cycle [ 15 ]. A stimulating effect of PGF2α on luteal angiogenesis has been described in bovines [ 36 , 37 ]. Our previous studies revealed that E2 regulates the expression of the endometrial PTGFR gene and protein in the pig, and indicated the involvement of PGF2α-PTGFR signaling in angiogenic changes within the endometrium [ 11 , 12 , 38 ].…”
Section: Discussionmentioning
confidence: 99%